Elevation of cardiac biomarkers in stroke is associated with pathological findings on cardiac MRI—results of the HEart and BRain interfaces in Acute Stroke study. Issue 2 (February 2023) - von Rennenberg, Regina; Herm, Juliane; Krause, Thomas; Hellwig, Simon; Stengl, Helena; Scheitz, Jan F; Elgeti, Thomas; Nagel, Sebastian N; Endres, Matthias; Haeusler, Karl Georg; Nolte, Christian H
Introduction: Cardiac biomarkers, such as high-sensitivity cardiac troponin T (hs-cTnT), are frequently elevated in ischemic stroke patients but the mechanisms underlying this elevation are insufficiently understood. We determined the presence of cardiac damage, assessed using cardiac magnetic resonance imaging (CMR), in stroke patients with elevated hs-cTnT and brain natriuretic peptide (BNP). Methods: This is a post hoc analysis of the prospective, investigator-initiated, cross-sectional HEart and BRain interfaces in Acute Stroke (HEBRAS) study. All patients underwent the measurement of hs-cTnT and BNP as well as gadolinium-enhanced CMR in the acute phase of ischemic stroke. We performed unadjusted and adjusted logistic regression models to assess the association between hs-cTnT and BNP elevation and the presence of pathological CMR findings. Results: Two hundred and thirty-three stroke patients (median age 67 years, 33% female) were included, of whom 43 (21%) had elevated hs-cTnT and 109 (47%) had elevated BNP. Hundred of the 233 (43%) patients had pathological findings on CMR had focal fibrosis as detected by late-gadolinium enhancement (LGE) in 51 (23%), left-ventricular hypertrophy (LVH) in 38 (16%), reduced LVEF in 32 (14%), and left-atrial dilatation in 34 (15%). After adjustment for potential confounders, both hs-cTnT (adjOR 5.0 (95%CI 2.1–11.7), p < 0.001) and BNP (adjOR 4.1 (95%CI 2.3–7.3), p < 0.001) were significantly associated with pathological findings on CMR. Hs-cTnT was associated with LGE, LVEF, and LVH, whereas BNP was associated with left-atrial dilatation and LVEF, LVH. Conclusion: Elevated cardiac biomarkers in acute stroke including CMR are strongly associated with pathological findings on CMR. In acute stroke patients, the elevation of cardiac biomarkers may identify patients who require a more thorough cardiology work-up.